2021
DOI: 10.1136/bmjsem-2021-001096
|View full text |Cite
|
Sign up to set email alerts
|

Discomfort, pain and fatigue levels of 160 cyclists after a kinematic bike-fitting method: an experimental study

Abstract: ObjectiveTo analyse rider’s subjective responses after a standardised bicycle ergonomic adjustment method.MethodsExperimental study of 160 healthy, amateur mountain bikers analysed previously and 30 days after a bike-fitting session. The main outcome measures were subjective comfort level (Feeling Scale, FEEL), fatigue (OMINI Scale) and pain (Visual Analogue Scale, VAS).ResultsAll variables demonstrated statistical significance between groups pre and post bike-fit session (p<0001). FEEL, OMNI and VAS-knee d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…One recent study on bicycling kinematics indicated an improvement in comfort and pain reduction on cyclists that were subjected to a kinematic bikefitting method using the rider's joint angular measurements as guidelines [28]. However, our results showed only short-term effects, so it is unknown if these improvements would endure through the passage of months after the bikefitting session.…”
Section: Introductioncontrasting
confidence: 57%
“…One recent study on bicycling kinematics indicated an improvement in comfort and pain reduction on cyclists that were subjected to a kinematic bikefitting method using the rider's joint angular measurements as guidelines [28]. However, our results showed only short-term effects, so it is unknown if these improvements would endure through the passage of months after the bikefitting session.…”
Section: Introductioncontrasting
confidence: 57%
“…Indeed, these systems are more precise 8 and they consider the kinematics in the three planes of space, in particular the movement of the knee in the frontal and transverse planes, which can lead to overuse injuries. 34 Some recommendations related to optimal joint angles have been provided in recent years by scientific studies and bike-fitting companies 26,63 but need to be validated by further experiments based on efficiency, injury prevention and comfort perception. In addition, it could be interesting to consider the effect of the angular velocity of the joints in bike-fitting studies.…”
Section: Discussionmentioning
confidence: 99%
“…These systems allow for the analysis of the lower and upper limb joint angles throughout the pedal stroke in two or three dimensions, and to relate them to standards recommended in the literature 19,20 or by bike-fitting companies. 26 In addition to joint angles, some motion capture systems offer a large number of movement-related variables, such as the angular velocity and acceleration of the joints, which provide information on the fluidity of the gesture. Lower limb joint velocity influenced muscle shortening velocity 27 and is particularly affected by the saddle height which is related to the joint stress, 28 but these variables are currently little used by specialists.…”
Section: Kinematicsmentioning
confidence: 99%
“…Using an alpha level of 5%, loss of follow-up limited in 10%, and power of 80%, we found that 19 participants in each team/group would be necessary for our study [ 20 ]. All calculations used G∗Power Software (University of Düsseldorf, Germany) as used in previous, our already published studies [ 21 ]. Table 1 shows the demographic and anthropometric characteristics of the sample before and after the quarantine period.…”
Section: Methodsmentioning
confidence: 99%